Conceptualising ‘Cultural Landscape Commons’: Retracing Ecological Thinking from the Swiss Alpine Landscape to Social-Ecological Systems - Nicole de Lalouvière (Revue de Géographie Alpine)
This paper retraces the fundaments of the ‘nature-culture’ divide within the study of Swiss alpine ‘cultural landscape commons’, showing how this notion was shaped by early ecological thinking expressed through environmental determinism, dynamic systems, and cultural ecology. These fields of research are seen as precursors to some of the currently dominant concerns within commons scholarship more broadly: defining system boundaries, distinguishing endogenous from exogenous forces, and identifying change patterns over extended spatiotemporal scales. Recent studies based in resilience thinking and the social-ecological systems (SES) framework reveal promising contributions from complexity studies, New Institutional Political Ecology (NIPE), and the analysis of change dynamics over the longue durée. A critical review of this research indicates possible ways forward to establish a conceptual framework for ‘cultural landscape commons’ based on a comparative, multi-scalar, and eco-evolutionary approach.